Sustainable Business Development Via Applying an Online Business Model for Gaining Benefit in Economics, Education, and Social Network - Rochmat Aldy Purnomo; Oksana Malynka; Adi Prananto (Universitas Muhammadiyah Ponorogo, 2023)
Regional development includes infrastructure and information technology. Infrastructure, Information and Communication Technology (ICT) is worse in rural areas and small towns in Indonesia. One of such areas is the village of Menowo located in Magelang, Central Java Province, Indonesia. The purpose of this research is to study a contemporary phenomenon of the Blogger Village within its real-life content. In this research, a case study is described: a young man who was born in the village has started an “online business community”. Now, people call the Village Menowo “The Blogger Village”. Since 2014, more than 50 people in the Blogger Village have got their own revenue accounts for hundreds of thousands of U.S. dollars per month. The Blogger Community has contributed to reducing unemployment in the village. The study has found that the Blogger Community can provide additional income for Magelang SMEs. Magelang SMEs can use the profit margin of their businesses to update hardware and software including Internet information sources from anywhere. The study provides new information related to the regional development, local development, and complement economic empirical studies of a research that has been done before. The applied research is beneficial for the Government of Magelang to determine and develop policies of the regional economic development of Magelang and to establish appropriate programs and activities for developing the economy of the area. The research will also help eliminate the overlap among the existing rules both at central and local levels, as well as among sectors and agencies.